Maiwa's Revenge; Or, The War of the Little Hand - Haggard, H. Rider (Henry Rider), 1856-1925 (Salt Lake City, UT : Project Gutenberg, 2006)
"Maiwa's Revenge; Or, The War of the Little Hand" by H. Rider Haggard is a novel written during the late 19th century. The book revolves around Allan Quatermain, a veteran hunter and adventurer, as he navigates the treacherous landscapes of Africa while engaging with various tribes and the challenges they present. The story is rich with themes of colonialism, the consequences of hunting, and the quest for justice. The opening of the novel introduces the protagonist, Allan Quatermain, as he embarks on a shooting excursion with his companions in Yorkshire. Throughout this portion, the elements of hunting and camaraderie are highlighted, showcasing Quatermain's exceptional shooting skills. The narrative transitions to foreshadow looming threats as it precedes the introduction of Maiwa, who carries a dire message from a character named John Every. The message warns Quatermain of danger from Wambe, a cruel chief, and sets the stage for themes of revenge, survival, and political intrigue in the African bush. The stage is effectively set for an adventurous tale that explores not only physical peril but also moral dilemmas and the bonds of friendship. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Maiwa%27s_Revenge
Release date is 2006-03-31
John Bickers, Dagny, Emma Dudding and David Widger
Keywords: Africa -- Fiction; Revenge -- Fiction; Hunting guides -- Fiction; Quatermain, Allan (Fictitious character) -- Fiction